1995
DOI: 10.1111/j.1432-1033.1995.tb20368.x
|View full text |Cite
|
Sign up to set email alerts
|

Activin A and Retinoic Acid Synergize in Cyclooxygenase‐1 and Thromboxane Synthase Induction During Differentiation of J774.1 Macrophages

Abstract: The murine macrophage cell line J774.1 was used to study the development of prostanoid biosynthesis under the influence of activin A and retinoic acid. Treatment of cells with 3 nM activin A for 48 h increased the biosynthesis of the prostaglandins E,, D,, FZa and thromboxane A, more than fourfold due to an induction of cyclooxygenase-1 while cyclooxygenase-2 was unaffected. Transforming growth factor-/I acted in a similar way. Retinoic acid, when present alone, was without effect on the total cyclooxygenase p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 44 publications
(21 reference statements)
2
16
0
1
Order By: Relevance
“…This effect of blocking activin A by follistatin was consistent with studies that have shown that activin A stimulates production of these cytokines, and other proinflammatory genes, in human, rat, and mouse mononuclear phagocytes in vitro (22,23,42). These data indicate a crucial role for activin A, and, consequently, for endogenous follistatin, in controlling the severity of acute inflammation and its subsequent actions.…”
supporting
confidence: 77%
“…This effect of blocking activin A by follistatin was consistent with studies that have shown that activin A stimulates production of these cytokines, and other proinflammatory genes, in human, rat, and mouse mononuclear phagocytes in vitro (22,23,42). These data indicate a crucial role for activin A, and, consequently, for endogenous follistatin, in controlling the severity of acute inflammation and its subsequent actions.…”
supporting
confidence: 77%
“…We suggest that the rapid but transient expression of Jun B mRNA contributes to the induced expression of COX-2. We recently reported on the participation of JunB mRNA expression in COX induction in a macrophage cell line [33]. Like the Jun-Fos heterodimers which mainly form the AP-1 factor JunB homodimers also possess trans-activity [34] and are thought to serve as tissue-specific activators of target genes regulated by AP-1.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, for example, have shown a clear relationship between retinoic acid and the generation of nitric oxide (NO) [9,12,28], prostaglandins [4,11] and the expression of cyclooxigenase 1 (COX-1) [23] and COX-2 [14,17]. All these mediators are involved in the generation or maintenance of sensitization and pain due to inflammation and are the targets for many painkillers studied in our lab among many others [7,10,26].…”
Section: Introductionmentioning
confidence: 99%